Drug-induced hypersensitivity syndrome with liver injury due to phenytoin: A case report - Wijaya, Lorettha; Adevita, Stella; Alvianto, Steven; Christiani, Yoseveline; Cahyadi, Alius; Yolanda, Raesa (UI Scholars Hub, 2024)
Background: Drug-induced hypersensitivity syndrome (DIHS) is a rare and severe systemic drug reaction characterized by skin involvement, internal organ complications, and hematologic disorders. Management of this condition is challenging due to its wide range of cutaneous manifestations and 10% mortality rate. Case Illustration: A 52-year-old male presented with widespread redness throughout his body with a prior history of regular phenytoin consumption. The rash continued to spread despite the patient’s abrupt discontinuation of the suspected medication. He was diagnosed with atypical DIHS according to J-SCAR criteria and was given high-dose corticosteroid. Drastic clinical improvement was observed after nine days of therapy, and complete resolution of the rash was achieved after 14 days. The steroid was stopped after four weeks, and no relapse was observed after four months of follow-up. Discussion: Discontinuing the suspected medication is the first crucial step in DIHS management. No specific pharmaceutical strategy has been established for this syndrome; however, systemic corticosteroids have been frequently prescribed as a first-line therapy. Steroids need to be tapered off slowly over 6–8 weeks, even upon clinical resolution, to prevent relapse. In the current case, the steroid was tapered off slowly over four weeks. The lack of relapse observed after steroid discontinuation could be due to the fact that the patient stopped consuming the suspected medication immediately. Conclusion: Education on the consequences of prescribing high-risk medications is important. Early detection and prompt cessation of offending medications are needed for better DIHS outcomes.